PENGARUH KEPUTUSAN PEMBELIAN JAMU TRADISIONAL DITINJAU DARI PENGETAHUAN PRODUK, KELOMPOK ACUAN, DAN PROMOSI DI KECAMATAN NGUTER SUKOHARJO (Studi Kasus Koperasi Indonesia Di Kecamatan Nguter Sukoharjo) - Daryono; Abdul Halik; Siti Mujanah (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this study is to examine the influence of Traditional Herbal Medicine Purchasing Decisions reviewed from product knowledge, reference groups and promotions in Nguter Sukoharjo sub-district which is the center of the traditional herbal medicine industry. The population in this study were consumers of traditional herbal medicine in Nguter Sukoharjo sub-district. Data collection was carried out through distributing questionnaires, documentation techniques used purposive sampling, the sample used 100 respondents with data collection using accidental sampling. The results of this study indicate that the variables of Product Knowledge, Reference Groups and Promotion have a positive influence on Purchasing Decisions. Keywords: Purchasing Decision, Product Knowledge, Reference Group and Promotion.